Analisis Beban Kerja Berlebih Pada Karyawan Ekspedisi Di Kota Pekanbaru - lamin, lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This research is motivated by the workload of employees from time to time that needs improvement. The sample in this study were 88 driver employees who worked in various expedition companies in the city of Pekanbaru. From the results of the SPSS test, the t count was 4.171 and also from the t table, the t table result was 1.987. So in this test, the t count was 4.171> t table 1.987 and the significance level was 0.000 <0.05. So the results of the hypothesis test in this study are that workload has a significant effect on employee performance. The relationship between workload and employee performance is negative, as evidenced by the results of the regression coefficient (b) of -0.719, which means that every increase in workload by one unit will reduce employee performance by 0.719 units. The R-square value (Coefficient of Determination) of 0.326 means that the contribution of the workload variable to employee performance is 32.60%